Blame Covid-19 and Ignore the Long History of Industrial Standardisation in Agriculture: Supermarket and GLOBALG.A.P. Standards, Exploitation of Migrant/Refugee Farmworkers, and Marginalisation of Small-Scale Farmers in Turkey - Atasoy, Yıldız (The International Journal of Sociology of Agriculture and Food, 2024)
This paper examines the resilience of small-scale farmers in Turkey who are facing an expanding industrial model in agriculture that is deepening the structural conditions of marginalisation and exclusion. This type of model is vulnerable to supply-chain disruptions due to various world-historical conjunctures, including the Covid-19 pandemic and the war in Ukraine, resulting in unprecedent hikes in agro-industrial-input and market-food prices, as well as food insecurity. Drawing on official documents and pre-pandemic interviews, the paper situates the resilience of these farmers within the state-planned expansion of agro-industrialisation directed towards boosting market- and export-based earnings. This industrial model is based on imported agro-inputs, land commodification, and contraction of village resources, as well as registration and standardisation as a condition for market access. It is further characterised by racially segmented agricultural labour markets, and exclusion of unregistered farmers and their food. The paper explores the structural constraints that emerge from an expanding industrialisation in agriculture, and considers how small-scale farmers might adapt to these conditions while co-existing with agro-industrialisation.